(untitled) (Janaki Medical College Journal of Medical Science, 2020)
Autism is a heterogeneous, neuro-developmental syndrome where patient shows various disorders, collectively known as autism spectrum disorders (ASDs). It mostly begins in infancy or during the first three years of life and has been found more in boys than in girls. The symptoms of ASD often include language regression, motor regression, and loss of bowel and bladder use. ASD also affects the feeding habit of children, with rates up to 74% as compared to normally developing children. Among different problems related to feeding, food selectivity is one of the key problems as it is directly linked with inadequate nutrition. Different factors affecting food selectivity are restrictive and repetitive behaviors, sensory modulation disorder, sensory over responsively, frequent illness /physical discomfort, and family preferences of food. Food selectivity among the children with ASD has been reported to be as high as 46- 89% as compared to typically developing children. Enough research on linkage of food selectivity with age and other factors is yet to be confirmed. Knowledge and awareness in parents regarding autism and food selectivity may help immensely to diagnose and address feeding problems in ASD at early stage.